REGIONAL ASPECTS OF MANAGERIAL SYSTEM OF PRODUCTION SPHERE ECOLOGIZATION AS INTEGRAL PART OF ENVIRONMENAL ECONOMICS - Zhanna S. Tikhonova (Advanced Engineering Research, 2011)
Actual aspects of the system development of the production sphere state regulation are presented. The state authorities system as a development and organization basis of the public environmental protection policy has been constructed. The public regulatory system of the production sphere ecologization at the regional level has been developed. Basic lines of the production sphere ecologization are analysed.